Sport prothesis bersus skiing prothesis - Bruhin, B. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
This is a case study about a high level alpine skiing athlete (3times medalist at the World Championships 2013). Since he was 6 years the athlete has a trans-tibia amputation on his right leg. The goal of this work was to analyze the EMG Signals and the ground reaction forces on both legs with two types of prostheses (sport prosthesis vs. skiing prosthesis).